ANAEROBIC LACTATE RESISTANCE OF A CROSS TRIATHLETE’S BODY - Liparova, Svetlana (European Scientific Journal, ESJ, 2014)
Monitoring of athletes and assessment of their current performance capacity is an integral part of the training as well as the whole training process. It requires an individual approach of the coach and the athletes who should know their assets as well as their limits. Testing provides us with the opportunity to assess the current state of an athlete’s body and their resistance to the load. These findings subsequently represent the basis for the evaluation of the training effect of the load, for adaptation of the training units and setting further course of the training process (Cillik & Tataruch, 2013). In our study, we discuss the resistance of a cross triathlete’s body to the load. We used a lactate test – 4x2 km with gradually increasing load. All the tests were performed in laboratory conditions at Matej Bel University in Banská Bystrica. We were able to identify the triathlete’s individual thresholds (aerobic threshold = AeT, anaerobic threshold = AT) by using the lactate test outcomes as a base. Our findings were subsequently correlated with the selected parameters from the training logs. The main research method was the regression and correlation analysis of the time series. The results obtained by mathematical statistics were subjected to the substantive analysis. The results and findings show that it is necessary to adjust the ATC and to time the increase of the AT towards the peak of the season. Training zones of various sports had different impact on the changes in the AT curve with different time lags as well as various levels of statistical significance (see the results). The most significant positive correlations of volume indicators and speed changes in the AT appeared during the second time lag. In addition to the cycling discipline, positive correlation of volume indicators appears also five months before the ascent of the AT curve. On the contrary, negative impact of the volume indicators appeared with the lag of one mesocycle.